2019
DOI: 10.31348/2019/2/1
|View full text |Cite
|
Sign up to set email alerts
|

Normal Tension vs High Tension Glaucoma: An Overview

Abstract: The study provides an up-to-date overview of pathogenesis, functional and structural changes in normal tension glaucoma (NTG) and its differences from high tension glaucomas (HTG). The authors point to less known facts which make both diagnostic groups different. First of all, there are electrophysiological findings that verify pathology in the complete visual pathway in HTG in contrast to NTG where the retinal ganglion cell response is relatively normal but the abnormalities are in the visual pathway. This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Ostatní korelace mezi VD a průtokovými parametry byly nevýznamné [10]. Na odlišnosti mezi NTG a HTG jsme upozornili v jiných pracích [11,12]. Zajímalo nás, zda budou zjistitelné určité změny mezi HTG a NTG i při hodnocení prokrvení oka.…”
Section: Diskuzeunclassified
“…Ostatní korelace mezi VD a průtokovými parametry byly nevýznamné [10]. Na odlišnosti mezi NTG a HTG jsme upozornili v jiných pracích [11,12]. Zajímalo nás, zda budou zjistitelné určité změny mezi HTG a NTG i při hodnocení prokrvení oka.…”
Section: Diskuzeunclassified
“…Furthermore, genetic differences can be presumed [ 52 , 53 ], and the peripapillary vessel density differs between HPG and NPG [ 54 ]. Lešták et al reported discrepancies in the results of pattern electroretinogram, pattern visual evoked potentials as well as functional magnetic resonance imaging between HPG and NTG [ 55 ]. On this basis, they assumed changes at different points of the visual pathway in both entities [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intraocular pressure (IOP) is a very important parameter in the pathophysiology of glaucoma, especially primary open-angle glaucoma [1]. Traditionally, glaucoma is suspected in a patient when their IOP is above 21 mm Hg, although there are a significant number of glaucoma patients with IOP measurements below this value (normotensive glaucoma) [2,3]. In any case, regardless of the type of glaucoma, it involves loss of nerve fibres in the optic nerve, causing visual field loss [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, glaucoma is suspected in a patient when their IOP is above 21 mm Hg, although there are a significant number of glaucoma patients with IOP measurements below this value (normotensive glaucoma) [2,3]. In any case, regardless of the type of glaucoma, it involves loss of nerve fibres in the optic nerve, causing visual field loss [2,3]. Glaucoma is the second leading cause of blindness in the world, with an estimated global prevalence of 3.5% in people aged 40-80 years.…”
Section: Introductionmentioning
confidence: 99%